The social anatomy of adverse childhood experiences and aggression in a representative sample of young adults in the U.S. (February 2019) - Mumford, Elizabeth A.; Taylor, Bruce G.; Berg, Mark; Liu, Weiwei; Miesfeld, Noelle
Abstract: Objective The current study assesses the effect of adverse childhood experiences on later aggression and violence across young adult relationships contexts, including intimate partners, friends, or strangers. Method Surveys were conducted with a nationally representative sample of young adults ages 18–32, drawn from the AmeriSpeak panel, a probability-based panel with coverage of 97% of U.S. households. The weighted study sample is 2284 young adult respondents, of whom 1561 reported being in an intimate partnership. Results Rates of verbal aggression perpetrated by young adults declined with the intimacy of the relationship, such that aggression against a partner (72%) exceeded aggression directed at friends (43%) and strangers (34%). Similar rates of physical violence (about 9%) were reportedly perpetrated against partners, friends, and strangers. Adjusting for a range of personal characteristics, both adverse childhood experiences and recent stressors in these young adult lives exhibited direct associations with verbal and physically aggressive outcomes. Conclusions In models of verbal and physical aggression across relationship contexts, childhood adversity exhibits lasting effects unaccounted for by important proximal life circumstances, including recent life stressors, mental health, and substance use behaviors. These results provide empirical insights for clinical treatment of young adults prone to aggressive conflicts as well as input to positive youth development programming to foster healthy approaches to conflict.